Fracture risk after three bariatric surgery procedures in Swedish obese subjects: up to 26 years follow‐up of a controlled intervention study - Ahlin, S.; Peltonen, M.; Sjöholm, K.; Anveden, Å.; Jacobson, P.; Andersson‐Assarsson, J. C.; Taube, M.; Larsson, I.; Lohmander, L. S.; Näslund, I.; Svensson, P‐A.; Carlsson, L. M. S. (Journal of internal medicine, 2020)
Background Previous studies have reported an increased fracture risk after bariatric surgery. Objective To investigate the association between different bariatric surgery procedures and fracture risk. Methods Incidence rates and hazard ratios for fracture events were analysed in the Swedish Obese Subjects study; an ongoing, nonrandomized, prospective, controlled intervention study. Hazard ratios were adjusted for risk factors for osteoporosis and year of inclusion. Information on fracture events were captured from the Swedish National Patient Register. The current analysis includes 2007 patients treated with bariatric surgery (13.3% gastric bypass, 18.7% gastric banding, and 68.0% vertical banded gastroplasty) and 2040 control patients with obesity matched on group level based on 18 variables. Median follow‐up was between 15.1 and 17.9 years for the different treatment groups. Results During follow‐up, the highest incidence rate for first‐time fracture was observed in the gastric bypass group (22.9 per 1000 person‐years). The corresponding incidence rates were 10.4, 10.7 and 9.3 per 1000 person‐years for the vertical banded gastroplasty, gastric banding and control groups, respectively. The risk of fracture was increased in the gastric bypass group compared with the control group (adjusted hazard ratio [adjHR] 2.58; 95% confidence interval [CI] 2.02–3.31; P < 0.001), the gastric banding group (adjHR 1.99; 95%CI 1.41–2.82; P < 0.001), and the vertical banded gastroplasty group (adjHR 2.15; 95% CI 1.66–2.79; P < 0.001). Conclusions The risk of fracture is increased after gastric bypass surgery. Our findings highlight the need for long‐term follow‐up of bone health for patients undergoing this treatment.